Facile approach to benzo[d]imidazole-pyrrolo[1, 2-a]pyrazine hybrid structures through double cyclodehydration and aromatization and their unique optical properties with blue emission. Issue 12 (18th February 2020) - Bae, Gi Hun; Kim, Suzi; Lee, Na Keum; Dagar, Anuradha; Lee, Jeong Hwa; Lee, Jeeyeon; Kim, Ikyon
Abstract : A modular approach to polycyclic N-fused heteroaromatics is described. Abstract : A modular approach to polycyclic N-fused heteroaromatics is described. Acid-catalyzed reactions of various 1-(2-oxo-2-arylethyl)-1 H -pyrrole-2-carbaldehydes with several o -phenylenediamines provided facile access to a number of new benzo[ d ]imidazole-pyrrolo[1, 2- a ]pyrazine hybrid structures through double cyclodehydration and aromatization. Optical characterization of the synthesized compounds revealed unique emission properties, with deep blue emission in the aggregated and solid states, and a dramatic substituent effect was observed. Fusion of an additional benzene ring into the benzo[4, 5]imidazo[1, 2- a ]pyrrolo[2, 1- c ]pyrazine scaffold resulted in a remarkable increase in the intensity of blue fluorescence from the solution along with good cell permeability and negligible phototoxicity, indicating the potential for bioimaging applications.